Fixed angle device comparison in young femoral neck fractures: Dynamic hip screw vs dynamic helical hip system. Issue 2 (February 2022) - Marchand, Lucas S.; Butler, Bennet; McKegg, Phillip; DeLeon, Genaro; O'Hara, Nathan N.; Lebrun, Christopher T.; Sciadini, Marcus F.; Nascone, Jason W.; O'Toole, Robert V.; Slobogean, Gerard M.
Highlights: Operative treatment of young femoral neck fractures results in a high complication rate. There is no difference in the rate of non-union and conversion to arthroplasty between DHS and DHHS. DHHS may allow for less clinically significant shortening of the femoral neck as compared to the DHS. DHHS may be a suitable device to manage the young femoral neck fracture, without increased complication risk. Abstract: Introduction: Femoral neck fractures in the young patient present a unique challenge. Most surgeons managing these injuries prefer a fixed angle implant, however these devices are fraught with problems. A dynamic hip screw (DHS) is one such fixed angle device that risks malreduction through rotational torque during screw insertion. To avoid this risk some surgeons utilize a dynamic helical hip system (DHHS), however little is known about the complication profile of this device. We hypothesized that the complication rate between these two devices would be similar. Patients and Methods: All patients presenting to a single tertiary referral center with a femoral neck fracture were identified from a prospectively collected trauma database over an 11-year period. Patients were included if they were less than 60 years of age, treated with a DHS or DHHS, and had at least 6 months of follow-up. Demographic data, injury characteristics, and post-operative complications were obtained through chart review. Standard statistical comparisons were made between groups. A total of 77 patients met inclusion criteria. Results: Average age of patients was 38 years (range: 18–59) and 56 (73%) were male. The DHS was used in 37 (48%) patients and the DHHS was used in 40 (52%) patients. Demographic data including average age, gender, body mass index, and smoking status did not differ between the groups. There were 29 (39%) total complications of interest (femoral neck shortening >5 mm, non-union requiring osteotomy, conversion to THA, and osteonecrosis. There were 19 (51%) complications in the DHS group and 10 (25%) in the DHHS group ( p  = 0.01, risk difference 25%, 95% CI 7–43). Comparisons of the individual complications about the DHS and DHHS cohort did not reach statistical significance for non-union (8% vs 3%) or THA (16% vs 13%) ( p  = 0.33, p  = 0.64, respectively) but a difference was detected in the rate of shortening (27% vs 10%; p  = 0.05). Conclusion: This study demonstrates a high risk of complication when managing young femoral neck fractures in line with prior literature. The major complication rate of non-union requiring osteotomy or fixation failure resulting in THA was no different between the two groups, but the rate of shortening was greater the DHS group. This data suggests the DHHS may be a suitable device to manage the young femoral neck fracture and without increased risk of complication.